2010
DOI: 10.1111/j.1463-1326.2010.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of treatment response in type 2 diabetes: assessing the role of patient heterogeneity

Abstract: The response to treatment for type 2 diabetes typically varies among individuals within a study population. This variation is known as heterogeneity of treatment response. We conducted a comprehensive literature review to identify factors that account for heterogeneity of treatment response in patients treated for type 2 diabetes. Three databases (PubMed, EMBASE and Cochrane Library) were searched for articles published in the last 10 years describing investigations of factors associated with treatment respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
2
24
1
2
Order By: Relevance
“…Multivariate logistic regression analysis showed that, in addition to postprandial CPR index, male sex, shorter duration of diabetes, absence of family history of diabetes, lower BMI, lower HbA1c, administration of a lower number of oral hypoglycemic agents (OHA) and no insulin use before admission were significantly related to good glycemic control, which is largely in line with the results of previous studies [14,15]. Accordingly, these results indicate that the predictive value of postprandial CPR index is relatively small.…”
Section: Acknowledgementsupporting
confidence: 88%
See 1 more Smart Citation
“…Multivariate logistic regression analysis showed that, in addition to postprandial CPR index, male sex, shorter duration of diabetes, absence of family history of diabetes, lower BMI, lower HbA1c, administration of a lower number of oral hypoglycemic agents (OHA) and no insulin use before admission were significantly related to good glycemic control, which is largely in line with the results of previous studies [14,15]. Accordingly, these results indicate that the predictive value of postprandial CPR index is relatively small.…”
Section: Acknowledgementsupporting
confidence: 88%
“…All data are expressed as mean ± SD, and significance levels for all tests were α = 0.05 in those trials. Although several studies have examined the correlation between CPR level and treatment outcome [14,15], the correlation remains to be established and there are few available data, especially in the Japanese population. The present study showed an association between baseline CPR and future glycemic control in the Japanese population, using our cohort with a relatively large sample size and long duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Poor HbA1c control in African Americans has also been reported in the USA, though our study found no such disparity in black African/Caribbean people 14 16 25 26…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, the global prevalence of obesity is higher in women than in men (Kelly et al, 2008). Finally, there is a sex specific response to anti-diabetic drugs in patients with type 2 diabetes (Cantrell et al, 2010).…”
mentioning
confidence: 99%